Особливості мови програмування Java та хмарних технологій - Ілляшенко, І. Б. (ХНУРЕ, 2024)
This article demonstrates the benefits of using cloud computing in Java based software as an important component of modern web development. Cloud computing is considered so revolutionary because it frees companies from maintaining their own servers, paying for a huge IT department and being responsible for cyber security in a rapidly changing security environment. It enables companies to quickly deploy and manage applications, minimizing infrastructure costs and ensuring optimal performance. Cloud computing is another area of the IT market that is the future and where Java is not only used, but often the main language. This paper describes an attempt to predict the future of Java and cloud computing based on the current situation.
Keywords: хмарні технології; cloud computing